LEGAL PROTECTION VERSUS LEGAL CONSCIOUSNESS (The changing Perspective in Law and Society Research) - Hakim, Muhammad Helmy (Pascasarjana UIN ANTASARI Banjarmasin, 2016)
Considering the important role of historical, cultural, social, and attitudinal aspects in the study of law, there has been a shift from instrumental law to constitutive law. While instrumental law considers law beyond the social and cultural spheres, constitutive law integrally embraces law, politics, ideology, and action. Legal consciousness is an important asset for marginalised people who are at high risk of discriminative treatments in occupational and social life. Not only will they are legally aware of their rights and obligations at works, they will have adequate knowledge of where and how to name, blame, and claim in case mistreatment do occur. Legally proficient will allow them build legal protection which is not adequately provided by the authorized bodies.